THE KEY ROLE OF PRECESSION CYCLE MODULATION IN THE ALTERNATION OF LATE PLEISTOCENE GLACIAL AND INTERGLACIAL EPOCHS - Vakulenko N.V.; Monin A.S.; Sonechkin D.M. (My University, 2003)
This paper shows that the 100-ka-long periodicity in the alteration of Late Pleistocene glacial and interglacial epochs was mainly controlled by the precession cycle modulation (related to the 100-ka-long eccentricity cycle) supplemented with a contribution from the obliquity cycle modulation.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен